Random Accessible Hierarchical Mesh Compression for Interactive Visualization - Courbet, Clement; Hudelot, Celine (Computer graphics forum, 2009)
This paper presents a novel algorithm for hierarchical random accessible mesh decompression. Our approach progressively decompresses the requested parts of a mesh without decoding less interesting parts. Previous approaches divided a mesh into independently compressed charts and a base coarse mesh. We propose a novel hierarchical representation of the mesh. We build this representation by using a boundary‐based approach to recursively split the mesh in two parts, under the constraint that any of the two resulting submeshes should be reconstructible independently. In addition to this decomposition technique, we introduce the concepts of opposite vertex and context dependant numbering. This enables us to achieve seemingly better compression ratios than previous work on quad and higher degree polygonal meshes. Our coder uses about 3 bits per polygon for connectivity and 14 bits per vertex for geometry using 12 bits quantification.